Sustained Effects of Memory and Lifestyle Interventions on Memory Functioning of Older Adults: An 18-Month Follow-Up Study - Chan, Agnes S.; Cheung, Winnie K.; Yeung, Michael K.; Lee, Tsz Lok (Frontiers in Aging Neuroscience, 2018)
Background: There has been much research devoted to examining the short-term effects of different interventions for improving memory functioning of older adults with memory complaints. Nevertheless, very few studies have examined the long-term effects of these interventions. Thus, the present study compared the sustained effects of a conventional memory intervention and a Chinese lifestyle intervention on improving memory functioning in older adults. Methods: Twenty-nine older adults who were aged 60 years and older and had memory complaints were recruited. Each completed ten weekly sessions of the Dejian Mind-body Intervention (DMBI; n = 11) or Memory Intervention (MI; n = 18) approximately 18 months ago. Participants’ verbal and visual memory functioning and their subjective impression of the changes of their memory performance and physical and psychological health status were evaluated. Results: Results showed significant improvements in memory in both intervention groups at the follow-up assessments when compared with baseline. In addition, older adults in both intervention groups perceived improved memory performance, and physical and psychological wellness at follow-up, with the DMBI group reporting significantly greater improvements in physical health compared to the MI group. Conclusion: Altogether, the present study provides supportive evidence that the DMBI and MI might be two effective remedies for older adults to improve or preserve their memory functioning with relatively sustained effects.